An analysis of water samples surrounding swine farms in Timis County – A practical guide - Valentin L. Ordodi; Crina Laura Moșneang; Romeo T. Cristina (Medicamentul Veterinar, 2013)
The most important role in biological soil pollution is allocated to the untreated waste water used to ground’s fertirigation from livestock farms, and in particular of swine units. Applying of arbitrary measures, and national and European legislation’s non-compliance are main factors that often makes from this issue a public health problem by the great impact it can generate and create in large agglomerations and animals. The diluted manures are able to affect the quality of the environment mainly by: nitrous oxide, ammonia, methane, hydrogen sulphide, volatile organic compounds, etc. and they, being administered in soils, may cause epizootic and epidemiological aspects and also those relating to environmental protection. In this respect it rise the need for all livestock farms to apply appropriate measures for certain manure treatment, different to species of animals and depending on the collection and discharge systems used. This paper is an original research work and it intends to be also a practical guide to follow for those interested in field research of environmental pollution. There are presented current investigation methodologies of water’s quality from swine farms vicinity in Timis County. In four chapters are presented: primary water analysis methodology, the determination of chlorides, nitrates and phosphates for each substance being presented methodology, kits and reagents necessary specific results and their interpretation and conclusions for each study. The last chapter was allocated to the description of the potentially polluting compounds determination by GC-MS technique.